2001
DOI: 10.1046/j.1365-2567.2001.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of conformational stability of hen lysozyme to
induction of type 2 T‐helper immune responses

Abstract: SUMMARYIt is important to identify characteristics that confer on proteins the potential to induce allergenic sensitization and allergenic disease. Protein allergens carry T-cell epitopes that are capable of inducing a type 2 T helper (Th2) cell response. There is limited information regarding factors that govern the allergenicity of proteins. We previously reported that a decrease in the conformational stability of hen-egg lysozyme (HEL) enhanced its capacity to activate HEL-speci®c T cells owing to the incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 49 publications
2
47
0
2
Order By: Relevance
“…Because protein unfolding may be a crucial step in intracellular Ag processing, the conformational stability of the protein Ag is important in determining the immune response. In a previous study using modified hen egg white lysozyme (HEL), we found that the T cell-triggering response and, therefore, the immune response, were governed by the degree of conformational stability of the protein Ags (18,19). This finding was supported by a study using derivatives of snake toxin with different stabilities, which found that Ag presentation was controlled by the stability of the toxin (20).…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…Because protein unfolding may be a crucial step in intracellular Ag processing, the conformational stability of the protein Ag is important in determining the immune response. In a previous study using modified hen egg white lysozyme (HEL), we found that the T cell-triggering response and, therefore, the immune response, were governed by the degree of conformational stability of the protein Ags (18,19). This finding was supported by a study using derivatives of snake toxin with different stabilities, which found that Ag presentation was controlled by the stability of the toxin (20).…”
mentioning
confidence: 84%
“…The immunization experiments using lysozyme were performed according the methods of So et al (19), with slight modification. Five mice were injected i.p.…”
Section: Measurement Of Serum Ab Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, self-protein sequences (including human antibody germ line sequences) have the potential to be recognized as foreign, as a consequence of occurring in a conjugated protein entity alone. Observations related to this possibility have been made in murine models, where modifications in protein conformational stability (53) or susceptibility to lysosomal proteolysis (54) have been shown to contribute to immunogenicity. Another example is the c o n j u g a t i o n o f a h e n e g g l y s o z y m e ( H E L ) t o phosphorylcholine.…”
Section: Mechanisms Of Immunogenicitymentioning
confidence: 99%